Proceedings of the third international conference on soft computing for problem solving : SocProS 2013, Volume 1 - Pant, Millie; Deep, Kusum; Nagar, Atulya; Bansal, Jagdish Chand (Advances in Intelligent Systems and Computing,, 2014)
The present book is based on the research papers presented in the 3rd International Conference on Soft Computing for Problem Solving (SocProS 2013), held as a part of the golden jubilee celebrations of the Saharanpur Campus of IIT Roorkee, at the Noida Campus of Indian Institute of Technology Roorkee, India. This book is divided into two volumes and covers a variety of topics including mathematical modelling, image processing, optimization, swarm intelligence, evolutionary algorithms, fuzzy logic, neural networks, forecasting, medical and health care, data mining etc. Particular emphasis is laid on soft computing and its application to diverse fields. The prime objective of the book is to familiarize the reader with the latest scientific developments that are taking place in various fields and the latest sophisticated problem solving tools that are being developed to deal with the complex and intricate problems, which are otherwise difficult to solve by the usual and traditional methods. The book is directed to the researchers and scientists engaged in various fields of Science and Technology.